2019
DOI: 10.30773/pi.2019.02.26.1
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: An Ocular Biomarker for Diagnosis of Attention Deficit Hyperactivity Disorder

Abstract: Objective Biomarkers of attention deficit hyperactivity disorder (ADHD) are crucial for early diagnosis and intervention, in which the identification of biomarkers in other areas of the body that represent the immature brain of children with ADHD is necessary. The present study aimed to find biomarkers of ADHD in the retina and assessed the relationship between macular thickness of the retina and cortical thickness of the brain in children with ADHD. Methods Twelve chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In recent years, few studies have explored macular thickness in ADHD. 2,5 In line with our findings, a recent study analyzed macular thickness in children with ADHD and found no significant difference in the ADHD group as compared to controls. 5 However, in another study, Bae et al found increased macular thicknesses in the ADHD group.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In recent years, few studies have explored macular thickness in ADHD. 2,5 In line with our findings, a recent study analyzed macular thickness in children with ADHD and found no significant difference in the ADHD group as compared to controls. 5 However, in another study, Bae et al found increased macular thicknesses in the ADHD group.…”
Section: Discussionsupporting
confidence: 91%
“…Many scientists continue to search for biological markers that might guide the diagnosis of ADHD and elucidate its etiology. 2 For this purpose, researchers have frequently used different neuroendocrine and neuroimaging techniques to define particular abnormalities related to this disorder. [2][3][4][5] There is general agreement regarding the atypical brain structure findings associated with ADHD on neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations